2002
DOI: 10.1093/nar/gkf417
|View full text |Cite
|
Sign up to set email alerts
|

The role of template-primer in protection of reverse transcriptase from thermal inactivation

Abstract: We compared the thermal stabilities of wild-type recombinant avian myeloblastosis virus (AMV) and Moloney murine leukemia virus (M-MLV) reverse transcriptase (RT) with those of mutants of the recombinant enzymes lacking RNase H activity. They differed in resistance to thermal inactivation at elevated temperatures in the presence of an RNA/DNA template-primer. RNase H-minus RTs retained the ability to efficiently synthesize cDNA at much higher temperatures. We show that the structure of the template-primer has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
69
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 63 publications
3
69
1
1
Order By: Relevance
“…Gerard et al 8) and we 9) have found that T/P-mediated stabilization of AMV RT was more potent than that of MMLV RT, suggesting that AMV RT has higher affinity toward the T/P than MMLV RT. Recently, Arezi et al discovered five novel mutations (Glu69 !…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Gerard et al 8) and we 9) have found that T/P-mediated stabilization of AMV RT was more potent than that of MMLV RT, suggesting that AMV RT has higher affinity toward the T/P than MMLV RT. Recently, Arezi et al discovered five novel mutations (Glu69 !…”
mentioning
confidence: 62%
“…7) Gerard et al have found that elimination of the RNase H activity of RT markedly enhanced the thermal stability of reverse transcription activity. 8) We have found that the reduction of reverse transcription activity of RT enhanced the thermal stability of RNase H activity. 6) Because RNase H activity is not required for in vitro cDNA synthesis, genetically engineered MMLV RT lacking RNase H activity is now widely used as a tool to synthesize cDNA.…”
mentioning
confidence: 94%
“…Both Gerard et al 22) and our own laboratory group 13) have found that T/P-mediated stabilization of AMV RT was more potent than that of MMLV RT, suggesting that AMV RT has higher affinity toward the T/P than does MMLV RT. Arezi et al discovered five novel mutations (Glu69!…”
Section: Discussionmentioning
confidence: 88%
“…Formamide at 10% inhibited PCR amplification by non-engineered Taq DNA polymerase, but increased the activity of the genetically engineered thermostable variant AmpliTaq DNA polymerase. 19,21) This suggests that genetically engineered thermostable MMLV RT variants [22][23][24] might also be highly resistant to DMSO and formamide effects.…”
Section: Discussionmentioning
confidence: 99%
“…The thermostability of MMLV RT was first improved by eliminating RNase H activity. [3][4][5] Recently, Arezi and Hogrefé increased thermostability by random mutagenesis in combination with activity screening at high temperature and generated a highly stable multiple variant, E69K/E302R/W313F/L435G/N454K 6) (In this report, mutation of a residue, e.g. Glu69 to Lys, is designated Glu69→Lys, and the MMLV RT variant, e.g.…”
mentioning
confidence: 99%